Perceptions of the Importance of English in Physics Teaching Careers: A Survey - Sarah, Siti; Maghfirah, Nurul Azri; Wahyunengsih, Wahyunengsih (DIKSI: Jurnal Kajian Pendidikan dan Sosial, 2025)
Since English improves academic communication, facilitates access to worldwide scientific sources, and supports professional development in international contexts, it has become an essential skill in physics education. Finding out how physics instructors and students perceive the importance of English in physics education and professional growth is the aim of this study. Forty-eight physics education students and 27 physics teachers participated in a quantitative survey. A validated survey with 50 Likert-scale items (Cronbach's Alpha = 0.84) was used to gather the results. Statistical methods that were both descriptive and inferential were used. The findings show that both groups had favorable opinions of English's involvement, with physics teachers indicating greater levels of perceived importance (M = 4.38) than students (M = 3.98). Professional communication, career advancement, and access to global scientific information were among the main perceived advantages. However, problems with qualified English language training and institutional assistance continued. The study concludes that, while taking local contexts into consideration, institutional strategies should support English literacy as a critical component of physics education.